Implementation of Police Professional Code of Ethics Sanctions for Serious Violations - Ramlah Ramlah; Basrawi Basrawi; Rika Rika; Sukma Sukma; Fatima Fatima; Nia Nia (Faculty of Law, Universitas Sembilanbelas November Kolaka, 2024)
The police code of ethics is regulated in the Chief of Police Regulation (Perkap) No. 14 of 2011, namely Personality Ethics; is the moral attitude of Polri members towards their profession based on the call of worship as religious people, State Ethics; is the moral attitude of Polri members who uphold the ideological and constitutional foundations of the Republic of Indonesia, namely Pancasila and the 1945 Constitution of the Republic of Indonesia and Institutional Ethics; is the moral attitude of Polri members towards the institution which is a place of devotion and should be upheld as a physical and spiritual bond of all Bhayangkara people with all their dignity and honor. But in reality, many police officers commit violations, especially serious violations, such as domestic violence, LGBT, sexual harassment, violence and other criminal acts. Therefore, this encourages the author to analyzethe sanctions for violators of the serious code of ethics in the Police. The research method used is empirical normative, namely juxtaposing the rules with the facts in the field, and the normative juridical method, namely the library approach method by studying statutory books and other legal scientific works. This legal research found that the application of sanctions for serious violators of the code of ethics must go through procedures that have been determined in the code of ethics regulations.